Folliculectomy for the treatment of pre-ovulatory follicular stasis in three illegally captured West Coast green geckos (Naultinus tuberculatus) to enable wild rehabilitation. - Gartrell BD; Jolly M; Cree A; Short E; Hori T (Taylor and Francis Group, 2024)
CASE HISTORY: In 2023, the New Zealand Department of Conservation seized 63 endemic reptiles that were being held without a permit. This group included three adult female West Coast green geckos (Naultinus tuberculatus) that had been illegally removed from the wild 2 years earlier. They had been held in an outdoor enclosure with a pair of goldstripe geckos (Woodworthia chrysosiretica). CLINICAL FINDINGS: On physical examination, all three geckos had at least two soft palpable masses in the coelom. Repeated ultrasonographic examination over several months confirmed the diagnosis of pre-ovulatory follicular stasis (POFS) in each gecko, and in subsequent weeks, more ovarian follicles developed in each animal. LABORATORY FINDINGS: All three geckos were negative on culture of cloacal swabs for Salmonella spp., and negative on PCR assay of a cloacal flush for Cryptosporidium spp., despite other reptiles in the seized group showing positive results for multiple Salmonella spp., and one other gecko being positive for Cryptosporidium parvum, subtype IIcA5G3. TREATMENT AND OUTCOME: For all three geckos, para-midline ventral coeliotomy was performed under general anaesthesia, and folliculectomy of degenerate ovarian follicles was performed. Post-operative complications were seen in all three animals, which developed suture-line infections following disruption of normal skin shedding and entrapment of shed keratin in the surgical sites. A second surgery was undertaken to remove impacted keratin and caseous inflammatory material from the surgical wounds of all three animals and buried sutures were placed to close the coelomic wounds. The geckos were treated with 20 mg/kg ceftazidime IM every second day for 2 weeks post-operatively. Subsequent ecdysis (skin shedding) occurred without complication and the geckos were released back to the wild 10 months after admission. CLINICAL RELEVANCE: The recommended treatment for POFS in reptiles is ovariectomy, which is not appropriate for wild animals. The use of folliculectomy to resolve preovulatory follicular stasis should be considered for animals where retaining reproductive ability is essential.
Keywords: Diplodactylidae; follicular stasis; herpetofauna; reproductive biology